1989
DOI: 10.1111/j.1399-302x.1989.tb00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of immunodominant antigens of periodontopathic bacteria in human periodontal disease

Abstract: Sonicated whole cell extracts and outer membrane proteins (OMP) from Bacteroides gingivalis and Veillonella parvula were analysed by the immunoblot technique using sera from 103 patients with various forms of periodontal disease and from 31 control subjects. B. gingivalis sonicate contained 12 major bands (75-14 kDa) of which the 46, 27 and 14 kDa antigens reacted more frequently with sera from adult and young adult patients with severe periodontitis compared with sera from controls and mild periodontitis pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…The same sera recognized protein bands between 95 and 55 kDa and at 36 and 27 kDa from an A. actinomycetemcomitans sonicate. Human antibody reactivity has been reported for 55-, 47-and 40-kDa surface proteins of P. gingivalis (13) and for 75-, 57-, 51-, 46-, 35-and 19-kDa outer membrane proteins of P. gingivalis (40). Genco et al (16) reported reactivity of immune mouse sera with 43-^ 33-, 29-to 31-and 13-to 16-kDa antigens of fl gingivalis.…”
Section: Discussionmentioning
confidence: 99%
“…The same sera recognized protein bands between 95 and 55 kDa and at 36 and 27 kDa from an A. actinomycetemcomitans sonicate. Human antibody reactivity has been reported for 55-, 47-and 40-kDa surface proteins of P. gingivalis (13) and for 75-, 57-, 51-, 46-, 35-and 19-kDa outer membrane proteins of P. gingivalis (40). Genco et al (16) reported reactivity of immune mouse sera with 43-^ 33-, 29-to 31-and 13-to 16-kDa antigens of fl gingivalis.…”
Section: Discussionmentioning
confidence: 99%
“…Another major protein they detected at 47 kDa may correspond to the 48-or 46-kDa proteins that were found to be prominent in the present study. Watanabe et al (46) have detected a 46-kDa antigen from P. gingivalis sonicated whole-cell extracts and outer membrane proteins that reacts more frequently with sera from patients with severe periodontitis. This antigen may be equivalent to the 46-kDa protein detected in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of an elevated antibody response to P. gingiualis whole cells in individuals with a history of periodontitis has been known for some time, the nature of the moieties on the surface of the organism, particularly the protein antigens, which are recognised by these antibodies has only recently become evident and a number of putative immunodominant antigens are now being identified [6][7][8][9][10][11][12][13][14][15]. We recently examined the immunoreactivity of the surface proteins of P. gingivalis W83 using sera from a case:control study of adult periodontitis [16].…”
Section: Introductionmentioning
confidence: 99%